A short period of high-intensity interval training improves skeletal muscle mitochondrial function and pulmonary oxygen uptake kinetics - Christensen, P. M.; Jacobs, R. A.; Bonne, T.; Flück, D.; Bangsbo, J.; Lundby, K. (Journal of Applied Physiology, 2016)
The aim of the present study was to examine whether improvements in pulmonary oxygen uptake (VO2) kinetics following a short period of high-intensity training (HIT) would be associated with improved skeletal muscle mitochondrial function. Ten untrained male volunteers (age 26 ± 2 yr; mean ± SD) performed six HIT sessions (8-12 × 60 s at incremental test peak power; 271 ± 52 W) over a 2-wk period. Before and after the HIT period, VO2 kinetics was modeled during moderate-intensity cycling (110 ± 19 W). Mitochondrial function was assessed with high-resolution respirometry (HRR), and maximal activities of oxidative enzymes citrate synthase (CS) and cytochrome c oxidase (COX) were accordingly determined. In response to HIT, V?o2 kinetics became faster (t: 20.4 ± 4.4 vs. 28.9 ± 6.1 s; P < 0.01) and fatty acid oxidation (ETFP) and leak respiration (LN) both became elevated (P < 0.05). Activity of CS and COX did not increase in response to training. Both before and after the HIT period, fast V?o2 kinetics (low t values) was associated with large values for ETFP, electron transport system capacity (ETS), and electron flow specific to complex II (CIIP) (P < 0.05). Collectively, these findings support that selected measures of mitochondrial function obtained with HRR are important for fast VO22 kinetics and better markers than maximal oxidative enzyme activity in describing the speed of the V?o2 response during moderate-intensity.